2008
DOI: 10.1152/physiol.00026.2008
|View full text |Cite
|
Sign up to set email alerts
|

Breathtaking TRP Channels: TRPA1 and TRPV1 in Airway Chemosensation and Reflex Control

Abstract: New studies have revealed an essential role for TRPA1, a sensory neuronal TRP ion channel, in airway chemosensation and inflammation. TRPA1 is activated by chlorine, reactive oxygen species and noxious constituents of smoke and smog, initiating irritation and airway reflex responses. Together with TRPV1, the capsaicin receptor, TRPA1 may contribute to chemical hypersensitivity, chronic cough and airway inflammation in asthma, COPD and reactive airway dysfunction syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
351
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(362 citation statements)
references
References 136 publications
9
351
0
Order By: Relevance
“…From the TRP superfamily, the main triggers in the airways are the TRPV and the TRPA ion channels, expressed on the C-fibers of sensory nerves [27,113115]. Nociceptive sensory neurons also take part in protective reflexes, including the cough and sneeze reflexes, and release inflammatory neuropeptides in the periphery upon stimulation by different environmental stimuli [113].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the TRP superfamily, the main triggers in the airways are the TRPV and the TRPA ion channels, expressed on the C-fibers of sensory nerves [27,113115]. Nociceptive sensory neurons also take part in protective reflexes, including the cough and sneeze reflexes, and release inflammatory neuropeptides in the periphery upon stimulation by different environmental stimuli [113].…”
Section: Resultsmentioning
confidence: 99%
“…From the TRP superfamily, the main triggers in the airways are the TRPV and the TRPA ion channels, expressed on the C-fibers of sensory nerves [27,113115]. Nociceptive sensory neurons also take part in protective reflexes, including the cough and sneeze reflexes, and release inflammatory neuropeptides in the periphery upon stimulation by different environmental stimuli [113]. The TRPA1 receptor antagonist GRC17536 has shown a statistically significant and clinical response in a Phase IIa clinical trial for the treatment of diabetic peripheral neuropathy [116]; however, an unpublished placebo-controlled study of GRC17536 in CC did not reduce 24 h cough frequency, cough VAS, or citric acid cough reflex sensitivity [21].…”
Section: Resultsmentioning
confidence: 99%
“…and inhaled chemical irritants (e.g., acrolein, toluene diisocyanate, etc.) (7,25,41,46). Immunohistochemical studies have shown that TRPV1 channels are also colocalized with certain sensory neuropeptides, such as tachykinins and CGRP, in the sensory terminals (51).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the transient receptor potential (TRP) superfamily of ion channels play a key role in the response of sensory neurons to inflammatory mediators and noxious chemical stimuli, initiating respiratory depression, cough, glandular secretions and other protective responses [10]. Jordt et al recently suggested that TRPA1 may function as an integrator of chemical and immunological stimuli modulating inflammation in the airways [10].…”
mentioning
confidence: 99%
“…Jordt et al recently suggested that TRPA1 may function as an integrator of chemical and immunological stimuli modulating inflammation in the airways [10]. Furthermore, chemical irritant-induced activation of TRPA1 may trigger the release of neuropeptides and chemokines in the airways, thereby exacerbating the cellular and tissue inflammatory response observed in allergic individuals [11].…”
mentioning
confidence: 99%